Evidence on Bullying, Safety, and Belonging in gifted students at secondary education school - Chia-Yen Hsieh (International Journal of Engineering Education, 2022)
In this study, we examine one commonly cited mechanism, the top dog/bottom dog phenomenon, which states that students at the top of a grade span (“top dogs”) have better experiences than those at the bottom (“bottom dogs”) for gifted students. Using an instrumental variables strategy introduced in Rockoff and Lockwood (2010) and a longitudinal data set containing student survey data for Kaohsiung City (in Taiwan) public secondary education school gifted students, we estimate the impact of top dog and bottom dog status on bullying, safety, belonging, and academic achievement by Multiple Regression. This article provides the first credibly causal evidence that top dog status improves the learning environment. We further find that the top dog effect is strongest in sixth grade and in schools with longer grade spans and that the top dog effect is not explained by new students to a school or student height. Finally, we find that the gifted students model is similar to the generally students model.